PERAN MANAJEMEN SEKOLAH DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK BERBASIS NILAI KEARIFAN LOKAL "MAJA LABO DAHU" DI PONDOK PESANTREN - Nurrahmaniah Nurrahmaniah; Septian Arief Budiman (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to analyze the role of school management in shaping student character based on the local wisdom value of "Maja Labo Dahu" at the Al-Kautsar Islamic Boarding School in West Nusa Tenggara (NTB). The value of "Maja Labo Dahu," which conveys shame and fear of committing acts contrary to religious, customary, and moral norms, is an important foundation for student character formation. This study uses a qualitative approach with a case study design to explore in-depth the managerial role of the madrasah principal in internalizing the value of "Maja Labo Dahu." The results indicate that school management plays a crucial role in shaping student character through planning, organizing, implementing, and supervising functions based on the Maja Labo Dahu value. The role of school management is evident in policy-making, human resource management, fostering school culture, and strengthening cooperation between the madrasah, the boarding school, and parents. The value of Maja Labo Dahu is internalized through teacher role models, discipline, the instilling of religious attitudes, responsibility, honesty, and compliance with applicable rules within the madrasah environment. This study concludes that effective school management can integrate the values ​​of Maja Labo Dahu local wisdom into various educational programs, thereby shaping the character of students who are religious, disciplined, responsible, honest, and have good morals. Therefore, strengthening school management based on local wisdom is a crucial strategy in building student character at the Al-Kautsar Islamic Boarding School in West Nusa Tenggara.